Strategi Mendisiplinkan Anak dalam Perspektif Praktisi dan Psikologi Anak - Zulfikar Ali Buto; Hafifuddin Hafifuddin (Pusat Studi Gender dan Anak - PSGA (Center for Gender and Child Studies) Institut Agama Islam Negeri Lhokseumawe, Aceh, 2021)
The development and growth of children are much influenced by intrinsic and extrinsic factors, the impact on children's habits which are often even difficult to control. When bad habits are always seen and felt, their response tends to be very fast and has a tremendous effect. This means that their good and bad habits are severed from habits through the visions and feelings that are present in their lives. This article describes strategies for disciplining children from a practical perspective and child psychology. Writing is done by using a library approach and analyzed descriptively so that readers can do it practically based on the psychology of their respective children. The result is that considering the different characteristics of the child according to the child's age, among them are trying to ignore the child when feeling bad, giving a good time guard, trying to get rid of favorite items by heart, trying to let the child face the consequences of their own actions, trying to express your feelings, try to give choices to children, try to give assignments to children, try to give understanding, try to reflect their behavior and try to reward children's good behavior. In addition to some of the things above, to practice discipline, the principles that must be carried out include setting long-term goals of caring for or educating children, thinking of ways to provide warmth (emotional security, unconditional love, verbal and physical affection) to children, guiding behavior and helping support children's expectations and encouraging children to think independently and understand children's thoughts and feelings.